Perceptions of IT Employees Regarding the Use of Disruptive Technologies in the Organisations in which They Work - Anamaria-Cătălina RADU; Andra Ileana DOBRESCU (Neicu); Larisa Gabriela OFIȚERU; Ivona STOICA (RĂPAN) (Communications of International Proceedings, 2020)
Worldwide, there is a convergence of web services and mobile technology. Applications that initially existed only on computers have also been developed for smart equipment, such as tablets and mobile phones. The applications’ need for portability led to the establishment of cloud services and cloud computing, which allow users to no longer invest in their own infrastructure, maintenance and upgrade, but merely lease from a certain data processing and storage services’ provider. In this paper we conducted a qualitative study through which we aimed to identify the general opinion of IT employees on disruptive technologies, and how they use them in the organisations in which they work. The qualitative analysis was performed among 10 experts working in the IT field.
Keywords: Disruptive technologies; cloud; qualitative study; IT&C.